Molecular subtype characteristics and development of prognostic model based on inflammation-related gene in lung adenocarcinoma - Xuelei Hu; Tengfei Jiang; Jinxiang Wang (Discover Oncology)
Abstract As one of the leading causes of death worldwide, lung adenocarcinoma (LUAD) currently lacks satisfactory treatment outcomes. The inflammatory process, closely associated with the formation of the tumor microenvironment and immune evasion, plays a crucial role in LUAD development. This study utilized data from public databases to analyze inflammation-related genes (INF) associated with prognosis in LUAD. Based on differentially expressed INF, molecular subtypes of LUAD were identified. Subsequently, a novel INF scoring system was developed to establish a prognostic model for LUAD patients, assessing its independence and reliability. Comprehensive evaluations, including immune microenvironment infiltration features, somatic mutation characteristics, and differences in immune therapy responsiveness, were conducted to characterize the prognostic model associated with INF. We further selected MMP14 from the screened INF targets for further in vitro experiments. Experiments such as western blot, qRT-PCR, colony-forming assay and Transwell assay confirmed that downregulation of MMP14 could inhibit the cloning, proliferation and invasion of lung cancer cells, thus confirming the results of bioinformatics. Our findings provide evidence from a new perspective on the role of inflammation in LUAD and offer new insights for clinical precision and personalized therapy.